We want to find the solution of the following inequality
![13\le(x)/((-5))+9](https://img.qammunity.org/2023/formulas/mathematics/college/vfxki6fog92h4xh3l4lx2vrdeuyoqjq6an.png)
To find the solution for this inequality, we can start by multiplying both sides by (-5).
When we multiply an inequality by a negative number, the "side" of the sign changes
![\begin{gathered} 13\le(x)/((-5))+9 \\ (-5)\cdot(13)\ge(-5)\cdot((x)/((-5))+9) \\ -65\ge x-45 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fj43fh15slz6uejm3rjdbyhapg20fqzi73.png)
And finally, we can add 45 to both sides of the equation to get our solution.
![\begin{gathered} -65\ge x-45 \\ -65+45\ge x-45+45 \\ -20\ge x \\ x\le-20 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yw38g4ipk2y58wo1ft85s7qskyrb08u5wn.png)
This is our final answer.
![x\le-20](https://img.qammunity.org/2023/formulas/mathematics/college/bx9pz5uzg1itlzas092j12xayo5smywybt.png)